MENINGKATKAN HASIL BELAJAR IPA MELALUI MODEL HANDS ON ACTIVITY PADA MURID KELAS V SD MUHAMMADIYAH 1 BONTOALA MAKASSAR - Yeni Marnia; Khaeruddin; Rahmatiah Thahir (Yayasan Nusantara Hasana Berdikari, 2023)
Science subjects are subjects related to systematic methods for learning about nature. The study of natural phenomena is the focus of the scientific discipline. In an elementary school science class, students learn about close natural knowledge. In previous studies, many students did not understand science lessons with the material